PENINGKATAN PRODUKTIVITAS BUDIDAYA IKAN NILA SALIN MELALUI IMPLEMENTASI MANAJEMEN RISIKO PADA KELOMPOK PETANI TAMBAK KECAMATAN DUKUHSETI, KABUPATEN PATI - Putri, Vini Wiratno; Wicaksari, Erisa Aprilia; Siyam, Nur; Rafinda, Ascariena (Universitas Mataram, 2024)
The aim of this service activity is to increase the self-resilience of pond farmers, due to very rapid environmental changes. Apart from that, this activity is also carried out as a form of implementation of the blue economy which is currently the focus of the government's attention. This is because fisheries cultivation is a business whose production activities are always faced with the threat of risk and uncertainty. The source of this uncertainty is usually a decrease in cultivation production results or price fluctuations. For this reason, it is necessary to carry out risk management to determine the appropriate risk map and strategy to handle production risks experienced by fisheries farmers. The partner for this activity is Pokdakan Berkah Nila Abadi, Dukuhseti District, Pati Regency. Dukuhseti District is an area for brackish water pond fish cultivation. Cultivating salted tilapia is the main commodity. Dukuhseti District is now the main supplier of salted tilapia fish in Central Java and on the island of Java. Seeing the production results and potential of brackish water pond fish cultivation, economically it has contributed to the local population to meet their financial needs. This activity method begins with identifying risks related to cultivation production results and price fluctuations. Furthermore, partners will be provided with training regarding preventive and risk mitigation strategies for managing saline tilapia ponds. It is hoped that regular mentoring and monitoring activities can increase partners' self-resilience abilities. So that partners become strong and superior in competing in the industry.